Matching and Optimization for the Parameter of Electric City Vehicle Powertrain - Li Wenwen; Sun Houhuan; Xu Xiaowen (Jixie chuandong)
Under the double pressures of energy crisis and environmental problems,the governments and the automobile enterprises have paid much attention to the pure electric vehicle which has advantages of zero emission,low noise and wide range of energy sources.Electric car is not very different from conventional cars,whether in the main structure or in the appearance.The main change is made in terms of drivetrain.Taking the pure electric city car as our research target,the power transmission system parameter is analyzed and designed,according to the vehicle parameters,power and economy requirements,the vehicle power system parameter is matched.The matched parameters of power system preliminarily is optimized from improving the transmission efficiency,taking the shortest time of acceleration and working conditions driving range maximum as optimization goal.The fitness function of transmission speed ratio is constituted of objective function and constraints condition by using a penalty function.The optimization is carried out by genetic algorithm,the optimal parameters of power system are obtained.